The Critical Analysis of Hiwar in Madrasah Ibtidaiyyah Textbook based on Core Competencies in the Republic of Indonesia - Suci Ramadhanti Febriani; Kddour Guettaoui Bedra; Rahmawati Rahmawati (Al-Ta'rib, 2022)
The Arabic teaching materials require adjustments to the core competencies listed in the Decrees of the Minister of Religious Affairs (Keputusan Menteri Agama/KMA) Number 183 and 184. Based on the previous statement, this study aims to examine hiwar teaching materials based on the KMA curriculum Number 183 and 184 in 2019. This research adopts a qualitative approach based on in-depth text analysis. This study’s data collection techniques include classification based on core competencies in the 2019 curriculum of hiwar texts for second grade in Madrasah Ibtidaiyyah. The study results indicate that this book has fulfilled four elements of competencies. First, spiritual attitude (KI-1) includes content that leads to spiritual improvement through an attitude of being grateful for God's blessings to all His creations. Second, social attitude (KI-2) includes mutual respect in interactions with friends and teachers through material content. Next, knowledge (KI-3) contains mastery of vocabulary and sentence structure in a conversation in each chapter, and finally, skills (KI-4) involve speaking skills through simple content for daily activities. The findings of this study show that the content of teaching materials that adopt the core competencies in KMA 183 and 184 has an impact on the variety of student experiences in producing Arabic orally. However, it is still necessary to improve content related to national values and cultural reinforcement for students